Antipsychotics: Mechanisms underlying clinical response and side-effects and novel treatment approaches based on pathophysiology. (1st August 2020) - Kaar, Stephen J.; Natesan, Sridhar; McCutcheon, Robert; Howes, Oliver D.
Abstract: Antipsychotic drugs are central to the treatment of schizophrenia and other psychotic disorders but are ineffective for some patients and associated with side-effects and nonadherence in others. We review the in vitro, pre-clinical, clinical and molecular imaging evidence on the mode of action of antipsychotics and their side-effects. This identifies the key role of striatal dopamine D2 receptor blockade for clinical response, but also for endocrine and motor side-effects, indicating a therapeutic window for D2 blockade. We consider how partial D2/3 receptor agonists fit within this framework, and the role of off-target effects of antipsychotics, particularly at serotonergic, histaminergic, cholinergic, and adrenergic receptors for efficacy and side-effects such as weight gain, sedation and dysphoria. We review the neurobiology of schizophrenia relevant to the mode of action of antipsychotics, and for the identification of new treatment targets. This shows elevated striatal dopamine synthesis and release capacity in dorsal regions of the striatum underlies the positive symptoms of psychosis and suggests reduced dopamine release in cortical regions contributes to cognitive and negative symptoms. Current drugs act downstream of the major dopamine abnormalities in schizophrenia, and potentially worsen cortical dopamine function. We consider new approaches including targeting dopamine synthesis and storage, autoreceptors, and trace amine receptors, and the cannabinoid, muscarinic, GABAergic and glutamatergic regulation of dopamine neurons, as well as post-synaptic modulation through phosphodiesterase inhibitors. Finally, we consider treatments for cognitive and negative symptoms such dopamine agonists, nicotinic agents and AMPA modulators before discussing immunological approaches which may be disease modifying. This article is part of the issue entitled 'Special Issue on Antipsychotics'. Highlights: Striatal dopamine D2/3 receptor blockade is essential for clinical antipsychotic response but within a therapeutic window. Off target effects at serotonergic, histaminergic, cholinergic & adrenergic receptors are responsible for key side effects. Current drugs act downstream of the major dopamine abnormalities and may worsen cortical dopamine function. New approaches include targeting dopamine synthesis and capacity, autoreceptors, trace-amine receptors and other mechanisms. Non-dopmaminergic approaches such as those addressing inflammation may prove to be disease modifying.